Associations between the placement on the starting blocks and indoor sprint performance - Reis, V. M.; Fazenda, L. M. (International Journal of Performance Analysis in Sport, 2004)
The development of an effective placement on the starting blocks is an important issue since this placement influences the sprint performance. The aim of the present study was to check the associations between the performance in a 60 m sprint and the following variables: distance between blocks (DBB), distance from the front block to the starting line (DFB), length of the first stride (LFS) and height of the subjects. Fifteen male sprinters performed an individual 60 m timed sprint on an indoor synthetic track. The DBB and the DFB correlated significantly with both the 20 m time and the 60 m time. The DBB and the DFB contributed, altogether, to explain ~56% of the variance of the 20 m and ~57% of the variance the 60 time. The standard error of the predictive models was ~3.2% for the 20 m time and ~1.7% for the 60 m time. It was concluded that the placement of the starting blocks affects significantly the performance in short sprint events and that the optimum position may result from a short distance between the front block and the starting line and from an increased distance between the blocks.